2019
DOI: 10.1039/c9tc02402f
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the nature of photoluminescence emission in the metal-halide double perovskite Cs2AgBiBr6

Abstract: The emission and absorption of Cs2AgBiBr6 are dominated by the strong carriers–phonon coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
223
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(248 citation statements)
references
References 52 publications
25
223
0
Order By: Relevance
“… 84 Cs 2 AgBiCl 6 has a pronounced long-lived component, previously attributed to the intrinsic PL lifetime driven by self-trapped excitons in this class of compounds ( Figure 7 a). 17 , 85 …”
Section: Resultsmentioning
confidence: 99%
“… 84 Cs 2 AgBiCl 6 has a pronounced long-lived component, previously attributed to the intrinsic PL lifetime driven by self-trapped excitons in this class of compounds ( Figure 7 a). 17 , 85 …”
Section: Resultsmentioning
confidence: 99%
“…Previous work attributed the sharp absorption peak in Cs 2 AgBiBr 6 to an exciton associated with the direct transition. 26,[52][53][54][55] However, there is also the possibility that these features in the pure compounds and mixed alloys are due to a narrow density of states at the band-edges. To explore this possibility, we computed the absorption spectra for Cs 2 AgSbBr 6 and Cs 2 AgBiBr 6 without excitonic effects (Fig.…”
Section: Electronic Structure and Bandgap Lowering Mechanismmentioning
confidence: 99%
“…[ 109 ] A recent study by Zelewski et al revealed that PL in this material occurs via color centers rather than a band‐to‐band transition. [ 110 ] The composition dicesium silver bismuth hexachloride (Cs 2 AgBiCl 6 ) has also been realized, exhibiting a larger bandgap in the range of 2.3–2.5 eV and a broad PL emission centered at ≈550 nm. [ 111 ] While dicesium silver bismuth hexaiodide (Cs 2 AgBiI 6 ) has not been realized in this bulk form, it has been recently demonstrated that Cs 2 AgBiI 6 nanocrystals can be synthesized either by anion exchange from Cs 2 AgBiBr 6 nanocrystals [ 112 ] or directly by the choice of appropriate precursors.…”
Section: Composition Defects and Microstructure And Their Impact Onmentioning
confidence: 99%